The relationship of sleep quality, work stress, nutritional status with work fatigue of employees in the process part of the palm factory - Azizi, Hilda Aprilia; Suraya, Rani; Harahap, Reni Agustina (Science Midwifery, 2024)
Work fatigue is one of the occupational health and safety problems which can be a risk factor for accidents while working. Fatigue can be caused by several factors, both internal and external factors. Internal factors include age, anemia status, length of service, sleep quality, and workload, while external factors include work shifts and hot work climate. The aim of this research is to analyze factors related to work fatigue in employees of the production section of PTPN IV Kebun Pabatu Tebing Tinggi. This research uses quantitative methods with a cross sectional design. The sampling technique is Stratified random sampling. The population and sample in this study were all 60 workers at PTPN IV Kebun Pabatu. Data was collected using a questionnaire and the variables studied included Nutritional Status, Environmental Quality, and Work Stress. The data was processed using the chi-square test using the SPSS version 20 application. The results of this study showed that there was a relationship between Nutritional Status and Work Fatigue (p value = 0.001), there was a relationship between Sleep Quality and Work Fatigue (p value = 0.004), and there was a relationship between Job Stress and Job Fatigue (p value = 0.003). It was concluded that the P-value <0.05 means that all variables have a significant relationship between nutritional status, work stress, and sleep quality and work fatigue. So it can be interpreted that all variables have a significant relationship between nutritional status, work stress, and sleep quality with work fatigue.